Critical infrastructures and the tragedy of the commons dilemma: Implications from institutional restructuring on reliability and safety. (11th February 2019) - Cedergren, Alexander; Lidell, Kristina; Lidell, Kristoffer
Abstract: Through the influence of neoliberal ideas, many critical infrastructures that used to be under public ownership have been opened up for market competition. Using the Swedish railway system as a case, this paper empirically explores whether such reforms have given rise to common‐pool resource problems, and discusses possible implications. The results show that institutional restructuring has created challenges related to balancing the use of the infrastructure with a sufficient level of maintenance. The paper concludes that the main value of analysing critical infrastructures from the perspective of common‐pool resources is the possibility of juxtaposing the way organizational and institutional interactions across scales generate both short‐term gains and long‐term negative side effects influencing reliability and safety.